Caregiving and mental well-being: the role of caregivers’ age and insomnia - Lam, Lawrence T. (Frontiers in Psychiatry, 2025)
ObjectiveWhile the impact of caregiving on physical and mental health has been studied, there remains a gap in understanding the relationship between caregiving and mental well-being within a robust theoretical framework. Moreover, existing research provides mixed findings regarding the burden experienced by caregivers and its impact on their health. To address this gap, we explore the association between caregiving and mental well-being, considering age as a potential moderator. Additionally, we examine the role of insomnia in this context.Methods and materialsThis population-based cross-sectional survey recruited adult residents in Macau. Participants’ caregiving roles were assessed, and their mental well-being was measured using the Short Warwick Edinburgh Mental Wellbeing Scale (SWEMWBS). Insomnia was also evaluated as a potential moderator by Insomnia Severity Index (ISI). The moderating effects of age and insomnia in the relation between caregiving and mental well-being were examined, with adjustments made for confounding variables using regression analyses.ResultsAfter controlling for confounders, the results indicated a significant interaction between caregiving roles and age group (β=0.84, s.e. = 0.10, t=8.42, p<0.001). Subgroup analyses revealed that the association between caregiving roles and mental well-being was significantly moderated by insomnia in the 18-34 age group (β=1.55, s.e. = 0.55, t=2.81, p=0.005), but not in other age groups. Younger caregivers seemed to benefit more from their caregiving roles in terms of mental well-being compared to older caregivers.ConclusionsThe results highlight the importance of considering age and insomnia when examining the impact of caregiving on mental well-being. The findings suggest that being a caregiver may have positive effects on mental health, particularly among younger individuals. Further research is needed to explore the underlying mechanisms and develop targeted interventions for caregivers of different age groups.